Acid‐Responsive Aggregated Gold Nanoparticles for Radiosensitization and Synergistic Chemoradiotherapy in the Treatment of Esophageal Cancer. Issue 19 (9th March 2022) - Luan, Siyuan; Xie, Rou; Yang, Yushang; Xiao, Xin; Zhou, Jianfeng; Li, Xiaokun; Fang, Pinhao; Zeng, Xiaoxi; Yu, Xiangrong; Chen, Meiwan; Gao, Huile; Yuan, Yong
Abstract: Radiotherapy and chemotherapy are limited by insufficient therapeutic efficacy of low‐dose radiation and nonspecific drug biodistribution. Herein, an acid‐responsive aggregated nanosystem (AuNPs‐D‐P‐DA) loaded with doxorubicin (DOX) is designed for radiosensitization and synergistic chemoradiotherapy. In response to the acid microenvironment of esophageal cancer (EC), small‐sized AuNPs‐D‐P‐DA forms large‐sized gold nanoparticle (AuNPs) aggregates in tumor tissues to hinder the backflow of AuNPs to the circulation, resulting in enhanced tumor accumulation and retention. Simultaneously, the AuNPs‐based radiosensitization is significantly improved because of the high concentration and large size of intratumoral AuNPs, while DOX are delivered and released specifically into tumor cells triggered by the acid microenvironment for chemo‐radio synergistic therapy. Acid‐responsive AuNPs exacerbate radiation‐induced DNA damage, cell apoptosis, cell cycle arrest, and low colony formation ability in vitro and enhance anti‐tumor efficacy in vivo compared to un‐responsive control. When combined with acid‐responsive DOX, the therapeutic efficacy of the formulation is further improved by their synergistic effect. After the treatment of acid‐responsive AuNPs plus radiotherapy, fatty acid metabolism is reprogrammed in xenograft models, which provides potential targets for further improvement of radiosensitization. In summary, the acid‐responsive AuNPs‐D‐P‐DA nanosystem leverages the radio‐ and chemotherapeutic synergies of AuNPs‐sensitized X‐ray irradiation and acid‐responsive DOX in the treatment of EC. Abstract : This study designs an acid‐responsive aggregated acid‐responsive aggregated nanosystem (AuNPs‐D‐P‐DA) for radiosensitization and synergistic chemoradiotherapy in the treatment of esophageal cancer. The nanosystem achieves tumor‐specific accumulation and controlled delivery of doxorubicin, both of which are triggered by the acid microenvironment. As a result, AuNPs‐D‐P‐DA leverages the radio‐ and chemotherapeutic synergies of AuNPs‐sensitized irradiation and acid‐responsive doxorubicin to maximize its therapeutic efficacy.